Plant biotechnology - Ignacimuthu, S. (New Delhi: Oxford & IBH Publishing Co., 1998)
Summarizes the latest scientific findings and methods in molecular biology, genetic engineering, and tissue culture, applied to agriculture. Emphasis is on cell and tissue culture, genetic transformation, and regeneration of transgenic plants. Contains chapters on the plant genome, plant genetic engineering, gene transfer systems for plants, and plant tissue culture, plus study outlines and questions.
Keywords: Plant genetic engineering; Plant biotechnology